First Middle Devonian bivalves from Argentina, new records from the Punta Negra Formation and insights on Middle Paleozoic faunas from Precordillera basin - Sterren, Andrea Fabiana (2015)
Middle Devonian bivalves from Argentina are reported for the first time, based on records of the Precordilleran Punta Negra Formation(Emsian?Frasnian?), San Juan Province. This finding is the youngest Devonian record of bivalves from southernmost South America. The impoverishedbivalve association in the Punta Negra Formation includes five shallow infaunal deposit feeders, i.e. Nuculites argentinum Sánchez,Anthracoleda (Pseudoleda) minuta Sánchez, Praenucula sp., Deceptrix sp. and Praectenodonta sp. The distribution of the Silurian?Devonian bivalvesfrom Precordillera shows a decreasing diversity trend during this interval, due to potential biases in sampling and paleoecology and thussuggesting that this trend might be apparent. Early and Middle Devonian bivalves from Precordillera show a strong cosmopolitan paleobiogeographicsignature, in contrast with other geographically related basins showing endemic (Malvinokaffric Realm) signals during the Devonian.Contrarily, an endemic composition is recorded in the Precordillera Basin when based on coeval Malvinokaffric groups such as ostracods and trilobites.Although more information is needed, the cosmopolitan character of Devonian bivalve assemblages from the Argentine PrecordilleraBasin might be interpreted under the light of a unique history driving biogeographic processes affecting different taxonomic groups in differentways.